Genotype and homology analysis of pathogenic and colonization strains of Candida albicans from hospitalized neonates - Jin-Zhen Su; Yu-Lan Yang; Rong Rong; Ben-Qing Wu (Elsevier, 2018)
Background: To detect the genotypes of pathogenic and colonization Candida albicans strains and to reveal whether there was a homologous relationship between these strains. Methods: Pathogenic and colonization isolates were collected from infants in the NICU of Shenzhen People's Hospital (Shenzhen, People's Republic of China). rDNA identification, multilocus sequence typing (MLST), and multi-loci variable number tandem repeat analysis (MLVA) were used for species confirmation, strain identification, phylogenetic tree clustering, and assessment of homology among the pathogenic and colonization strains. Results: All 48 isolates belonged to C. albicans species; 12 were collected from premature infants with fungal sepsis. These isolates generated 5 sequence types (ST1867, ST2551, ST2552, ST2937, and ST2945) and were designated as pathogenic strains. The other 36 isolates were collected from the infants without fungal infection; 9 sequence types were detected and designated as the colonization strains. In the phylogenetic tree, the upper branch consisted of a 4° clade composed of 20 colonization isolates designated to 3 strains, and 4 pathogenic isolates designated to 1 strain; a 5° clade composed of 8 pathogenic isolates designated to 3 strains; and a 4° clade consisting 1 pathogenic isolate designated to 1 strain and 4 colonization isolates designated to 2 strains. The lower branch consisted of a 3° clade composed of 6 colonization isolates designated to 2 strains and a control pathogenic isolate, and a 3° clade composed of 5 colonization isolates designated to 2 strains. Conclusion: Although there was no core ST detected to specify pathogenicity or colonization of C. albicans, the genotypes of the colonization strains were different from those of the pathogenic strains. Most of the colonization and pathogenic strains were highly homologous within their classifications while some pathogenic strains had genomes highly homologous with those of colonization strains and clustered in heterogeneous groups. Key Words: Candida albicans, cluster analysis, genotype, MLST, MLVA